Framing basic income in Australia: how the media is shaping the debate. Issue 4 (2nd October 2021) - Carroll, Leah; Engel, Susan
ABSTRACT: Universal basic income is an old idea that has experienced a surge in global attention. In many countries, it is creeping up the policy agenda as an alternative to traditional welfare. Yet, in Australia, the idea is mostly ignored by the two main political parties. Communication scholars have long contended that the media play a role in influencing opinion and setting the policy agenda. Using a framing approach, this study analyses how basic income was framed in 2018 by seven Australian newspapers and compares the results with those in countries where basic income has solidified a position in public discourse. We found that the mainstream media outlets in Australia are overtly hostile to the idea, which presents a significant obstacle to a universal basic income gaining legitimacy as a social policy.